Indeks Massa Tubuh Pada Penderita Diabetes Melitus Dengan Nilai Ankle Brachial Index - Dwi Priyantini; Ninik Ambar Sari; Prinka Arifiyah Hanggitriana (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
In patients with diabetes generally increased blood glucose levels if accompanied by excess body weight and long-lasting it can increase the risk of diabetic ulcer complications. The aim of the study was to determine the relationship between Body Mass Index (BMI) and Ankle Brachial Index (ABI) values in patients with type 2 diabetes mellitus at the Klampis Ngasem Surabaya Public Health Center. The research design was an analytic observational approach with a cross-sectional study. The sample in this study was 124 respondents selected using a purposive sampling technique. The instruments were in terms of scales, stature meters, digital sphygmomanometers, and observation sheets. The data were analyzed using Spearman's Rho Test with significance (0.05). The results of the research showed that there was a correlation between BMI and ABI values in patients with type 2 Diabetes Mellitus at Klampis Ngasem Surabaya Public Health Center Surabaya (Ï value = 0.000) with a correlation coefficient (r = -0.392). BMI is one of the factors that can affect the ABI value in diabetic patients. Itâ€™s expected that health workers will help DM sufferers improve their quality of life through DM disease management behaviors by implementing a healthy lifestyle in order to reduce the risk of complications that can arise due to diabetes mellitus.